Anti-ulcerative colitis effect of Calligonum comosum L'Hér. using rat model: Chemical, pharmacological and histopathological evidences - Hassan N. Althurwi; Mohammad Ayman A. Salkini; Gamal A. Soliman; Khalid M. Alharthy; Abubaker Hamad; Maged S. Abdel-Kader (Elsevier, 2023)
Calligonum comosum is a perennial shrub growing and widely used in traditional medicinal system in Saudi Arabia. The total phenolic content and in vitro antioxidant activity were compared between the water extract (WE) and methanol extract (ME). The protective potential against acetic acid (AA) induced ulcerative colitis (UC) was also evaluated in rats. The obtained results showed that the total phenolic content of the WE and ME were 8.378 ± 0.738 and 33.819 ± 0.488 µg/mL. The antioxidant properties of the two extracts were directly influenced by their total phenolic contents. The ME with higher phenolic contents and stronger antioxidant power was more effective than the WE in protection against AA-induced colitis. Phytochemical study of the ME led to the identification of three flavonoid derivatives: (-)-epi-catechin, quercetin-3-O-α-l-arabinofuranoside (Avicularin) and quercetin-3-O-β-d-glucuronide-6"-methyl ester by various spectroscopic methods. (-)-Epi-catechin was the major component while the other two compounds were obtained in minute quantities. The anti-ulcerative colitis effect of the ME can be explained by the presence of the antioxidant flavonoids since AA-induced colitis featured by imbalance between oxidant and antioxidant substances. Further support of such explanation was provided by HPLC quantification of (-)-epi-catechin in the ME and WE. The percentage in ME was higher than the WE but the difference was higher in term of Total Phenolic Content (TPC). These results support the traditional use of C. comosum as anti-ulcerative colitis.